Complementary detection strategies for circulating tumor cells in breast cancer: clinical implications of combining immunofluorescence and cytopathological staining - Jesenko, Tanja; Grasic Kuhar, Cvetka; Pisljar, Ziva; Miceska, Simona; Kloboves-Prevodnik, Veronika; Cemazar, Maja (Frontiers in Oncology, 2025)
BackgroundCirculating Tumor Cells (CTCs) serve as important biomarkers for disease monitoring and treatment response in patients with metastatic breast cancer. Their detection remains challenging because of their low abundance, phenotypic diversity and non-standardized mode of detection. Cytopathological Giemsa and Immunofluorescence (IF) staining can offer complementary approaches for CTC characterization. Giemsa staining enables assessment of cellular morphology, while IF allows for marker-specific identification, together providing a more comprehensive and accurate evaluation of CTCs.MethodsWe developed an IF staining protocol with antibodies against Cytokeratin (CK), vimentin (VIM), and Cluster of Differentiation 45 (CD45) to distinguish epithelial, mesenchymal, hybrid and hematopoietic cells for CTC detection and characterization and compared it with cytopathologic method of detection via Giemsa staining with regard to CTC detection rates and morphological detail.ResultsStudy was performed on the samples of 29 heavily pretreated patients with metastatic breast cancer (median duration of metastatic disease 19.4 months). Giemsa staining enabled the detection of a higher number of CTCs compared to our IF protocol. Lower detection rate was potentially due to the loss of fragile or loosely adherent cells during methanol fixation and IF staining. Additionally, in IF-stained samples, some CTCs presented faint nuclear signals, potentially impairing their recognition. The IF staining supported the identity of CTCs detected on Giemsa-stained slides by employing a three-color antibody panel-based approach and allowed detailed phenotypic discrimination and structural analysis of CTCs, including the identification of a distinctive CK polarization pattern suggestive of a transitional state during intravasation.ConclusionGiemsa and IF may thus be complementary rather than mutually exclusive and relying on a single detection approach could underestimate the true CTC burden. An integrative strategy combining both techniques may offer a more comprehensive view of CTC populations in metastatic breast cancer, thereby enhancing diagnostic precision.